13 International symposium on high current electronics: Tomsk, Russia, 25-29 July 2004; 7 International conference on modification of materials with particle beams and plasma flows - Kovalchuk B. Boris; Remnev G. Gennady (Tomsk, 2004)
400 Anniversary of Tomsk